LINGUISTIC INTERPRETATION OF EUPHEMISMS USING FOLK PROVERBS - Ibragimova Zamira Yuldashevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article focuses on the linguistic and cultural significance of euphemisms used in folk proverbs and the etymology of their origin